Angioedema: a rare and sometimes delayed side effect of angiotensin-converting enzyme inhibitors. Issue 4 (4th July 2019) - Davin, Laurent; Marechal, Patrick; Lancellotti, Patrizio; Martinez, Christophe; Pierard, Luc; Radermecker, Regis
Abstract: The effects of angiotensin converting enzyme (ACE) inhibitors result from the inhibition of the ACE (kininase II) to ultimately influence both the renin–angiotensin system and the degradation of the bradykinin (BK) metabolism. ACE inhibitors block the degradation of BK and substance P by ACE. In addition, an active metabolite of BK (Des-Arg9-BK) is catalysed by kininase I and its degradation is controlled in part by the conversion enzyme. These molecules have been associated with increased plasma extravasation associated with ACE inhibitors. ACE inhibitors are the leading cause of drug-induced Angioedema (AE). Symptoms of AE mainly occur after the first month of treatment by ACE. However, very late onset cases, sometimes after several years of stable therapy, are also described in the literature. It has been observed that patients previously stable under ACE inhibitor will most likely develop AE soon after the addition of another medication, including the combination of aspirin or non-steroid anti-inflammatory drugs with ACE inhibitor which has proved to be the most common cause, accounting for close to 50% of all AE cases related to ACE inhibitors. This side effect of ACE inhibitors, sometimes very late and rare, deserves to be recalled